2019
DOI: 10.1007/s00268-019-04952-w
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Parathyroidectomy Does Not Influence Renal Function After Kidney Transplantation

Abstract: Background Parathyroidectomy (PTx) is the treatment of choice for end-stage renal disease (ESRD) patients with therapy-resistant hyperparathyroidism (HPT). The optimal timing of PTx for ESRD-related HPT-before or after kidney transplantation (KTx)-is subject of debate. Methods Patients with ESRD-related HPT who underwent both PTx and KTx between 1994 and 2015 were included in a multicenter retrospective study in four university hospitals. Two groups were formed according to treatment sequence: PTx before KTx (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
(58 reference statements)
1
6
0
Order By: Relevance
“…In contrast, the median post‐PTx PTH level in our study was higher at 66.2 pg/mL in the post‐KT PTx group. Other studies with benign renal outcomes in post‐KT PTx reported similar postoperative median PTH levels of 7.7 pmol/L (73.3 pg/mL) [20] and 46.9 pg/mL [21]. PTH has a positive hemodynamic effect on renal blood flow and [26] we hypothesize that a higher postoperative PTH level may be appropriate in KT patients.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In contrast, the median post‐PTx PTH level in our study was higher at 66.2 pg/mL in the post‐KT PTx group. Other studies with benign renal outcomes in post‐KT PTx reported similar postoperative median PTH levels of 7.7 pmol/L (73.3 pg/mL) [20] and 46.9 pg/mL [21]. PTH has a positive hemodynamic effect on renal blood flow and [26] we hypothesize that a higher postoperative PTH level may be appropriate in KT patients.…”
Section: Discussionsupporting
confidence: 53%
“…Our study adds to existing reports that show the safety of post‐KT PTx on allograft function. Frey et al [19], van der Plas et al [20] and Bures et al [21]. Some studies have shown an adverse effect of PTx on allograft function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 Several studies reported a decline in allograft function following PTx 10 , 23-26 or the use of cinacalcet. 27 However, other studies found no changes in allograft function following PTx 8 , 23 , 28 , 29 or cinacalcet. 30 The discrepancy is partly due to variation in length of follow-up and a lack of a control group to adjust the confounding effect of tertiary HPT itself.…”
Section: Introductionmentioning
confidence: 95%
“…In this issue, Ivarsson et al and van der Plas et al studied the effects of parathyroidectomy on renal function after kidney transplantation and the incidence of cardiovascular events after parathyroidectomy in patients with secondary HPT, respectively [4,5]. Utilizing data from four university hospitals over a 21-year period, van der Plas et al compared renal function (as defined by glomerular filtration rate [GFR]) in patients, according to whether parathyroidectomy was performed before or after renal transplantation.…”
mentioning
confidence: 99%